Analisis Pengalaman Wisatawan Saat Mengunjungi Destinasi Wisata MICE Halal “Muslim Life Festival 2022” - Gantina Suciati; Titing Kartika; Adrian Agoes (Eduturisma, 2023)
Tourism activities will be worth the reward when visitors continue to carry out the obligations of things that have been determined in certain religious rules. In the context of Muslims, they will have certain needs when traveling for tourism. The research objective is to analyze a national event organized by PT.Lima Event entitled "Muslim Life Festival 2022". The research analyzes a phenomenon that occurs in society regarding interest in a lifestyle, sharia-based business management and the behavior of Muslim tourists' interest in visiting Halal MICE destinations in Indonesia. This research aims to (1) find out how an event can be held (2) find out the process of implementing Islamic values at the event and (3) find out the experiences and Islamic values that will be accepted by tourists. The research uses a qualitative descriptive analysis approach with a case study research method. The results of the study show (1) The Muslim Life Festival 2022 event management system can apply various rules regarding qualifications in properly planning MICE events. (2) Event organizers are able to properly implement Islamic values. (3) Tourist experiences can be described based on statements submitted by visitor informants. Further research can be carried out on other events with more comprehensive tourist experience indicators.